In Vivo Safety and Efficacy of Chalcone-Loaded Microparticles with Modified Polymeric Matrix against Cutaneous Leishmaniasis - Ariane de J. Sousa-Batista; Natalia Arruda-Costa; Wallace Pacienza-Lima; Felipe Carvalho-Gondim; Rosiane F. Santos; Silvia A. G. Da-Silva; Maria Inês Ré; Bartira Rossi-Bergmann (MDPI AG, 2022)
Current chemotherapy of cutaneous leishmaniasis (CL) is based on repeated systemic or intralesional administration of drugs that often cause severe toxicity. Previously, we demonstrated the therapeutic potential of biodegradable poly(lactic-co-glycolic acid) (PLGA) microparticles (MPs) loaded with 8% of the nitrochalcone CH8 (CH8/PLGA) prepared by a conventional bench method. Aiming at an industrially scalable process and increased drug loading, new MPs were prepared by spray drying: CH8/PDE with PLGA matrix and CH8/PVDE with PLGA + polyvinylpyrrolidone (PVP) matrix, both with narrower size distribution and higher drug loading (18%) than CH8/PLGA. Animal studies were conducted to evaluate their clinical feasibility. Both MP types induced transient local swelling and inflammation, peaking at 1-2 days, following a single intralesional injection. Different from CH8/PDE that released 90% of the drug in the ear tissue in 60 days, CH8/PVDE achieved that in 30 days. The therapeutic efficacy of a single intralesional injection was evaluated in BALB/c mice infected with Leishmania (Leishmania) amazonensis and golden hamsters infected with L. (Viannia) braziliensis. CH8/PVDE promoted greater reduction in parasite burden than CH8/PDE or CH8/PLGA, measured at one month and two months after the treatment. Thus, addition of PVP to PLGA MP matrix accelerates drug release in vivo and increases its therapeutic effect against CL.